Ethnobotanical survey of medicinal plants used by communities on the fringes of Budongo Central Forest Reserve, Uganda - Kahwa, Ivan; Omara, Timothy; Agaba, Mercy; Nuwagira , Upton; Olusoji Ajayi , Clement (Ethnobotany Research and Applications, 2025)
Background: The resurgence of interest in traditional medicine, amid growing antimicrobial resistance, underscores the need to document and preserve indigenous ethnobotanical knowledge. Budongo Forest Reserve in Western Uganda is a biodiversity hotspot with communities whose traditional medicinal practices remain underexplored. This study aimed to document medicinal plants used by communities around the Budongo Forest Reserve and their associated ethnomedicinal practices. Methods: A cross-sectional ethnobotanical survey was conducted in December 2023 among 25 respondents selected via snowball and purposive sampling. Data were collected using semi-structured questionnaires and open interviews, focusing on plant use, preparation methods, and disease treatment. Voucher specimens were identified and authenticated, and data were analysed using descriptive statistics, citation frequency, and preference ranking. Results: Seventy (70) medicinal plant species belonging to 34 families and 66 genera were documented as treatments for 43 different health conditions. Dominant families included Asteraceae (15.7%) and Fabaceae (8.6%). The most cited species were Erythrina abyssinica, Agapanthus africanus, and Hoslundia opposita, used to manage syphilis, ulcers, erectile dysfunction, and malaria. Leaves (56.2%) were the most used plant parts, with remedies prepared primarily by squeezing (34.7%), decoction (31.9%), or infusion (22.2%), and administered mainly orally (70.3%). Conclusions: Communities around Budongo Forest Reserve possess rich ethnomedicinal knowledge and are heavily reliant on native flora. Certain species’ high citation and preference scores underscore their cultural and therapeutic importance. Bioactivity-guided research is recommended to validate the therapeutic claims, particularly for under-investigated species with high local use values. Keywords: Ethnobotany, Traditional medicine, Medicinal plants, Budongo Forest, Uganda